2010
DOI: 10.2105/ajph.2010.193490
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From Evaluations of California's Statewide School Nutrition Standards

Abstract: Regulation of competitive foods improved school food environments and student nutritional intake. Improvements were modest, partly because many compliant items are fat- and sugar-modified products of low nutritional value. Additional policies and actions are needed to achieve more substantive improvements in school nutrition environments and student nutrition and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
154
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(165 citation statements)
references
References 48 publications
9
154
1
1
Order By: Relevance
“…The results thus support policy evaluations that concluded that policies were effective if they addressed all aspects of the school food environment. 29,33,34 The caveat, however, is that within-state correlation between laws makes it impossible to disentangle the 6 laws to identify the source of any effects. The observational design precludes us from making any causal inferences, but even if one could conclude that laws caused lower weight gain, one could not determine if the cause was because of the laws' cumulative impact or 1 law having an exceptionally strong impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results thus support policy evaluations that concluded that policies were effective if they addressed all aspects of the school food environment. 29,33,34 The caveat, however, is that within-state correlation between laws makes it impossible to disentangle the 6 laws to identify the source of any effects. The observational design precludes us from making any causal inferences, but even if one could conclude that laws caused lower weight gain, one could not determine if the cause was because of the laws' cumulative impact or 1 law having an exceptionally strong impact.…”
Section: Discussionmentioning
confidence: 99%
“…Dialogue on the topic has been limited by the lack of longitudinal evidence regarding the association between school nutrition policies and student weight status. Research has suggested that competitive food policies are associated with improvements in the school food environment, student dietary intake, or weight outcomes, [28][29][30][31][32][33][34] but most studies were cross-sectional or limited to individual states. A recent study reported no association between competitive food sales and weight gain, but it was based on school administrator surveys rather than independent review of codified laws.…”
mentioning
confidence: 99%
“…These data, as well as historical data from the US Centers for Disease Control and Prevention's state School Health Profiles (32) study, the School Health Policies and Programs Study (33,34) and USDA's SNDA-III (14) , support the view that the inconsistent approach to regulating competitive foods in schools needs improvement. The inconsistent approach to restricting competitive foods in schools has not led to universal changes in the availability of such foods nationwide, although several studies have demonstrated that state laws do affect student consumption and access to less healthful foods and beverages such as whole milk, sugar-sweetened beverages and high-fat/salty snacks (35)(36)(37)(38)(39) . And there is emerging, albeit mixed, evidence of the impact of state and/or district competitive food policies on BMI (40)(41)(42)(43)(44)(45) .…”
mentioning
confidence: 99%
“…And there is emerging, albeit mixed, evidence of the impact of state and/or district competitive food policies on BMI (40)(41)(42)(43)(44)(45) . Given that a number of studies (35)(36)(37)(38)(39)(45)(46)(47)(48)(49)(50)(51) have demonstrated strong competitive food and/or beverage policies can effectuate changes at the school level, it is expected that the availability of high-fat, high-energy, high-sugar foods and beverages in competitive venues will decline with nationwide standards governing competitive foods and beverages.…”
mentioning
confidence: 99%
“…One method to impact lifestyle changes, particularly for children attending public schools, is through legislation. For example, Woodward-Lopez, Gosliner, Samuels, Craypo, Kao, and Crawford (2010) assessed the impact of legislation establishing nutrition standards for foods and beverages that compete with reimbursable school meals in California through pre and post testing at 99 schools. Results indicated that the availability of nutrition standard-compliant foods and beverages increased, and the availability of noncompliant items had decreased.…”
Section: Obesity Interventionsmentioning
confidence: 99%